Handedness in the presence of prior knowledge: Effects of interhemispheric configuration on performance. (7th January 2023) - Markus, Andrey; Eviatar, Zohar
Abstract: The current study examined the effects of prior knowledge of the responding hand, and that of errors, on the configuration of interhemispheric balance. Prior knowledge was manipulated by instructing the participants to respond with one hand throughout a session (Blocked) or to select the responding hand according to the identity of the stimulus in each trial (Mixed). In addition, we examined how failures to inhibit responses within Logan's (1981) Stop Signal Response Task (SSRT) task affected the Response Times (RTs) of subsequent correct responses. The SSRT was modified to include visual stop signals, shown in Divided Visual Field (DVF), in order to examine the effects of errors committed by each hemisphere. The effects of prior knowledge were shown by absence of a dominant hand effect in the Blocked condition but were uniformly present in the Mixed condition. We also show that commission of an error in the peripheral VFs differentially affected subsequent RTs only in the absence of prior knowledge. We conclude that prior knowledge shifts interhemispheric configuration from the default dominance model to a more complex cooperative configuration.